Diplopia as the Initial Manifestation of Cerebral Vasculitis in a Patient with Systemic Lupus Erythematosus: Diagnostic Approach and Challenges - Audy Ariana; Awalia (Indian Journal of Forensic Medicine & Toxicology, 2022)
The term Neuropsychiatric systemic lupus erythematosus (NPSLE) encompasses all neurologic and or psychologic symptoms arising in patients with SLE after other causes have been ruled out. Cerebral vasculitis as a manifestation of NPSLE is a rare case with a very broad spectrum of clinical presentation and severity. We report a case of a female with cerebral vasculitis presenting with diplopia as its early manifestation. Diagnosing cerebral vasculitis remains challenging given that biopsy as the gold standard is an invasive procedure and may not be available in many settings. A high suspicion of diagnosis requires clinicians’ judgement in reviewing combination of detailed history taking, physical examination, neuroimaging, and other available supporting modalities.